Autotransplantation after primary bone repair of a recipient site with a large periradicular lesion: a case report. (16th August 2019) - Arbel, Y.; Lvovsky, A.; Azizi, H.; Hadad, A.; Averbuch Zehavi, E.; Via, S.; Ben Itzhak, J.; Solomonov, M.
Abstract: Aim: To describe a case of autotransplantation nine weeks after the extraction of a hopeless tooth with a large periradicular lesion, which enabled the healing of the recipient site. Summary: A 19‐year‐old male in generally good health was referred for evaluation of tooth 46. Clinically, there were class III mobility and sensitivity to percussion and palpation. There was a mesio‐lingual swelling and a single narrow deep pocket of 15 mm at the disto‐lingual aspect. CBCT imaging revealed a radiolucent area over 15 mm in diameter that extended from the mesial aspect of the mesial root of tooth 47 to the distal aspect of tooth 45. The radiolucent area was in proximity to the inferior alveolar canal and penetrated the buccal and the lingual cortical plates. The tooth was diagnosed with previously treated tooth, acute apical abscess and vertical root fracture. Tooth 46 was extracted, and a delicate curettage and drainage were performed. Nine weeks afterwards, a second surgery was performed: extraction of the impacted immature third molar (tooth 48). Immediately after the extraction, the tooth was replanted in the healing socket of tooth 46, and sufficient initial stability achieved. At a 1‐year follow‐up, the tooth had normal mobility, no sensitivity to palpation and percussion, and responded to thermal pulp testing. The soft tissue was normal, probing depths up to 3‐mm, without swelling or sinus tract. Radiographically, periapical healing at the recipient site was observed. Compared to the post‐operative periapical radiography immediately after the procedure, there was no change in the distal root dimensions. In the mesial root, development of the root length and a closed apex was demonstrated.